2006
DOI: 10.1016/j.clpt.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of cytochrome P450 2C19 in Mexican Americans: A cross-ethnic comparative study

Abstract: This is the first study to investigate CYP2C19 polymorphism in Mexican Americans. The frequencies of the CYP2C19*2 and *3 alleles in Mexican Americans were found to be significantly lower than in other ethnic groups. This genotypic pattern might be responsible for the lower rate of poor metabolizers in Mexican Americans compared with other ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 25 publications
9
61
4
1
Order By: Relevance
“…The CYP2C19*2 allele had a frequency of 7.9%, similar (P > 0.08) to Mexican-American, West Asian, and Southern and Eastern European populations (Luo et al, 2006;Kurose et al, 2012). The CYP2C19*2 allele frequency was statistically different from Western and Northern European; Southern, South-Eastern, and Southern Asian; Caucasian; and African populations (P ≤ 0.042), whose frequencies range from 14 to 29.8% (Kurose et al, 2012).…”
Section: Resultsmentioning
confidence: 90%
“…The CYP2C19*2 allele had a frequency of 7.9%, similar (P > 0.08) to Mexican-American, West Asian, and Southern and Eastern European populations (Luo et al, 2006;Kurose et al, 2012). The CYP2C19*2 allele frequency was statistically different from Western and Northern European; Southern, South-Eastern, and Southern Asian; Caucasian; and African populations (P ≤ 0.042), whose frequencies range from 14 to 29.8% (Kurose et al, 2012).…”
Section: Resultsmentioning
confidence: 90%
“…Calculated allele frequencies did not differ much from those reported earlier by other studies for Caucasians, as shown in Table 2. 17,18 Incidence of GVHD No statistic differences were found in the incidence of acute GVHD grade 2-4 for EMs, IMs and PMs with 28.2, 32.8 and 25%, respectively. The genotype of donors also had no significant influence on the incidence of GVHD grade 2-4 in patients.…”
Section: Frequency Of Ems Ims and Pmsmentioning
confidence: 94%
“…5 Asians possess higher frequencies of *2 (28.9-31.2%) than Caucasians (12.7%) and African Americans (18.2%). 6 The second most important PM allele is CYP2C19*3, which carries a G-A nucleotide substitution in exon 4, creating a premature stop codon. 7 The prevalence rate of *3 in Asians ranges from 5.7 to 9.6%, whereas in Caucasians it is only 0.9%.…”
Section: Introductionmentioning
confidence: 99%